Depths of despair: Experience report - Maria Joana Nunes de Azevedo (Archives of Depression and Anxiety - Peertechz Publications, 2021)
Between 2017 and 2019 I went through the experience of depression and consequently I developed anxiety. In the beginning, in the months of November and December 2017, I found myself in a deep despair, not knowing how to identify what was happening. As an intervention, I went through consultations with the psychologist, where I had conversations, writing and positive affirmations. After these consultations I improved and got out of my depressed state. Awareness in the consultations with the psychologist made me realize how far I was from who I am and from this contact with a professional I was able to gain clarity about my condition and learned techniques to maintain my self-care constant.